Musical interests and activities in children’s leisure time in Hungary and Bulgaria - VELIKOVA, MILENA STEFANOWA (Journal of Education Culture and Society, 2020)
Beneficial use of leisure time is extremely important as it helps to expand the horizons for intellectual growth, emotional experiences, and personal enrichment. The aim of this study is to establish the interests and needs for music in children’s leisure time. Music is very close to the emotional nature of children and therefore could stimulate and develop their mental and physical abilities. This report focuses on the place of music and art in students’ life and discusses how much of their free time is taken up with these pursuits. It also analyses the needs of such activities. Here the results from a study in which children between 9 to 17 years of age from Bulgaria and Hungary took part are presented. The type of musical activities preferred by the children in their leisure time and the correlation between the activities of choice and cultural differences are also studied. Understanding what music activities children favour in their leisure time is important because learning combined with the  arts builds long lasting social skills and educates on tolerance, creativity and discipline. This combination when used in work with children, helps children to develop ability for better self-expression, building up confidence, concentration, integration in the group, developing imagination, recognizing the  good and beautiful,  and increases their chances for success in life.